The Relationship between Aromatherapy and Mental Wellbeing: A Narrative Review - Almansour, Baraa (Unisia, 2022)
Mental disorders are patterns of behavioral or psychological symptoms that affect multiple areas of life; these disorders create distress for the person experiencing these symptoms. The search for the most effective and safe treatments is essential. Aromatherapy as a specialized segment of phyto-therapy have attracted the attention of many researchers as complementary method for treating patients with neurological and psychiatric complaint due to their low cost and ease of use. While, it could be practiced via inhalation or topical application and massage utilizing specific essential oils for several, minor, clinical uses as a natural way of healing a person’s mind, body and soul.